Growing Skull Fracture Following Monkey Bite - Deginal, Amaresh; Rao, Naveen; Balasubramanyam, K.; Changty, Siddaling (Indian Journal of Neurotrauma, 2005)
Most of the skull fractures in childhood heal without sequelae. Rarely, however the fracture site starts widening with time and appears to be growing, and is thus called growing skull fracture. Its late complication is called leptomeningeal cyst, which is practically cerebromeningeal cicatrix with loculated CSF. All most all reported cases are due to head trauma resulting from road traffic accidents or fall. Here we report a case of leptomeningeal cyst occurring one year after having been bitten by a monkey over the site.
Keywords: dural tear; growing skull fracture; leptomeningeal cyst; monkey bite; skull fracture